Highlights for Management of a Child with a Urinary Tract Infection - Sabeen Habib (International Journal of Pediatrics)
Urinary tract infections remain the most common bacterial infection in childhood. Escherichia coli is responsible for over 80% of Pediatric UTIs. Other common gram negative organisms include Kleibsiella, Proteus, Enterobacter and occasionally Pseudomonas. Signs and symptoms vary greatly by age of the patient becoming more specific as the child grows older. Even in the absence of specific signs a UTI should be included in the differential diagnosis of high grade fever. In younger children, presence of upper respiratory infections, otitis media or gastroenteritis does not eliminate the possibility of a UTI. Culture of the urine remains the gold standard for diagnosing UTIs. All males and females with well documented UTIs should be imaged for the presence of urological anomalies associated with UTI. Depending on patient's clinical symptoms and tolerance, therapy can be oral or parenteral as they have both been found equally efficacious. Healthcare professionals should ensure that when a child or young person has been identified as having a suspected UTI, they and their parents are given information about the need for treatment, the importance of completing any course of treatment and advice about prevention and possible long-term management.